Hubungan antara Lumbosacral Transitional Vertebra dan Degenerasi Diskus Lumbal pada Pemeriksaan MRI: Relationship between Lumbosacral Transitional Vertebra and Lumbar Disc Degeneration on MRI Examination - Aulia Ramadhani Simatupang; Laila Syalsabilah Pohan; Putri Salsabilah Ritonga; Anisah Dini Atika; Miftahul Jannah; Nirwana Claudia Br Sitepu; Rifky Audiansyah Pasaribu; Intan Maulina (Yayasan Cita Cendekiawan Al Khwarizmi, 2026)
Lumbosacral Transitional Vertebra (LSTV) is a congenital anatomical variation at the transition between the last lumbar vertebra and the sacrum that can affect the biomechanics of the lumbosacral spine. These biomechanical changes may increase mechanical stress on the overlying vertebral segments and accelerate lumbar disc degeneration. Lumbosacral disc degeneration is a major cause of low back pain, with high prevalence in the productive-age population and an impact on quality of life and productivity. Magnetic Resonance Imaging (MRI) is an imaging modality with high accuracy for evaluating soft-tissue structures of the spine, thereby playing an important role in identifying LSTV and assessing the degree of disc degeneration. This study used a systematic literature review method to analyze the relationship between LSTV and lumbar disc degeneration based on MRI findings. A literature search was conducted in PubMed, Google Scholar, ScienceDirect, and ResearchGate databases using the keywords